Woody Guthrie - Al Aumuller:::Photojournalist:::::::::::: (World Telegram)
Woody Guthrie with a guitar labeled "This machine kills fascists" in 1943. Guthrie was an American singer-songwriter and composer who was one of the most significant figures in American folk music. His work focused on themes of American socialism and anti-fascism. He inspired several generations both politically and musically with songs such as "This Land Is Your Land" and "The Ballad of Tom Joad" which Guthrie wrote after seeing the film "The Grapes of Wrath." Steinbeck supported Guthrie's music and message.